Review of Mammarenavirus Biology and Replication - Hallam, Steven J.; Koma, Takaaki; Maruyama, Junki; Paessler, Slobodan (Frontiers in Microbiology, 2018)
The family Arenaviridae is divided into three genera: Mammarenavirus, Reptarenavirus, and Hartmanivirus. The Mammarenaviruses contain viruses responsible for causing human hemorrhagic fever diseases including New World (NW) viruses Junin, Machupo, Guanarito, Sabia, and Chapare virus and Old World (OW) viruses Lassa, and Lujo virus. These two groups of arenaviruses share the same genome organization composed of two ambisense RNA segments. These segments contain four open reading frames (ORFs) that encode for four proteins: the nucleoprotein (NP), glycoprotein precursor (GPC), L protein (LP), and Z. Despite their genome similarities, these groups exhibit marked differences in their replication life cycles. This includes differences in attachment, entry, and immune evasion. By understanding the intricacy of replication in each of these viral species we can work to develop counter measures against human diseases. This includes the development of vaccines and antivirals for these emerging viral threats. Currently only the vaccine against Junin virus, Candid#1, is in use as well as Ribavirin for treatment of Lassa Fever (LF). In addition, small molecule inhibitors can be developed to target various aspects of the virus life cycle. In these ways an understanding of the arenavirus replication cycle can be used to alleviate the mortality and morbidity of these infections worldwide.